The potential of pineapple peel waste fermentation as antibacterial and antioxidant agents - Mawli, Rizka Efi; Putri, Devi Anggraini; Dewi, Maharani Putri; Alfaini, Galuh Nuri; Febriani, Afaf; Anggraini, Dwi Aprilia; Sutanto, Andri Kurniawan (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
The fermentation of pineapple peel waste can yield a product in bioactive compounds, including an eco-enzyme that serves as both an antibacterial and antioxidant agent. By utilizing the fermentation process, the extraction of phenolic compounds is enhanced through the action of degrading enzymes produced by microorganisms. This study aims to explore the potential of fermenting pineapple peel waste from with varying fermentation durations of one month (designated as EE-1) and three months (designated as EE-3) to assess their antibacterial and antioxidant properties. The method research is purely experimental methodology with several testing phases: the preparation of the eco-enzyme, a disc diffusion test for antibacterial activity, the determination of the minimum inhibitory concentration (MIC) using the resazurin microtiter assay (REMA), and the assessment of antioxidant activity through the DPPH test. The result showed that the eco-enzyme fermentation has a dark brown color for EE-1 and a light brown color for EE-3, with a pH range of 3 to 3.2 and a sour pineapple aroma. EE-3 exhibited the highest antibacterial and antioxidant activity. It demonstrated strong inhibition against Propionibacterium acnes at concentrations of 100and 102, with MIC values of 3.13 mg/mL for Staphylococcus aureus, 12.5 mg/mL for Staphylococcus epidermidis, and 6.25 mg/mL for P. acnes. The minimum bactericidal concentration (MBC) was found to be 25 mg/mL for all tested bacteria, while the antioxidant activity of EE-3 was indicated by an IC50 value of 1.95 mg/mL.